The contribution of the tennis foundation and Olympic values in the life and school education of ex project participants in Santiago City/RS/ Brazil - Rosa, Angelica Salbego da (2020)
Outdoor tennis is a way for education, develops values, encourages socialization and respect. The Tennis Foundation project uses the Olympic Values for individuals from the neediest communities, giving them the opportunity to change their lives through the tennis practice. A questionnaire was applied to evaluate the Tennis Foundation contribution and Olympic Values in life and in school education of seventeen (17) ex project participants, in Santiago City/RS/Brazil. Results showed the teacher importance and Olympic Values contribution in the participants’ life, as well as the opportunities of access into the job market.